Encontros de sangue: cultura da violência na região dos Vales dos Rios Araguaia e Tocantins 1830/1930 - Medeiros, Euclides Antunes de (2012)
This thesis sought to rebuild part of a rural culture, herein referred to as culture of violence from the historical narrative of the lifestyles and perceptions the inhabitants of remote regions in the region of the valleys around the Araguaia and Tocantins Rivers, a region consisting of the current state of Tocantins, former northern Goias, southern Pará and Maranhão, between 1830 and 1930. The historical representation woven into my narrative holds that that lifestyle and its representations, built by the rural folk at that time and in that space, are violent as a rule. This is the result of specific learning picked up through exposure to violence and such learning is embedded in the social memory of this region, and even in periods of relative tranquility this memory is brought to life by its inhabitants as required and in accordance with the interests of the individuals involved, which engenders and encourages new rounds of violence which, as a whole, have built a culture of violence.